Simply Delicious / Fahmiera Abdul Fatah... [et al.] - Abdul Fatah, Fahmiera; Mohd Zaini, Zarin Zalikha; Roger, Rebecca; Abdul Rahman, Siti Jaliha; Sebastian, Shirley Vanessa (2013)
Simply Delicious is business plan of a cafe serving Malay food in Malaysia, especially keropok lekor. Some call them fish fritters, fish sausages or fish sticks, fish crackers but in Malaysia, they are called keropok lekor. It is traditional fish sausage normally consumed as a morning and evening snack. Keropok lekor are actually made from processed fish meat mixed with salt and tapioca flour. This mixture is then hand rolled into sausage shaped around 6 to 10 inches long and immediately cooked. Name was chosen by our Financial Manager, Miss Shirley Vanessa Sebastian. The company’s name as Simply Delicious because of the taste of our main product which is refers to our keropok lekor. Miss Fahmiera Binti Abdul Fatah is the one that fuse of the Simply Delicious business. Our keropok lekor is unique and different from others keropok lekor. We have many type of keropok lekor. It comes in three main forms where it was original, crunchy and crunchy cheese keropok lekor. Original keropok lekor, will be cooked it in two ways which is fried and grill. Meanwhile, we try to innovatethe original keropok lekor into the namely crunchy keropok lekor. The substance in crunchy keropok lekor is still same with the original one but the crunchy keropok lekor is more crunchies and look like nuggets. We also add some flavour to our keropok lekor which is crunchy cheese keropok lekor. The cheese which diced into cube will pour into the fish mixture and then shaped it into a small size before being boiled and fried. All these three types of keropok lekor are frequently served with dipping sauces. Now, we are planning to open our business by using our own secret recipe. We hope that our business of keropok lekor will be expanded and get good responses from our customers.